Teacher Profesionalism in Improving Children’s Speech Ability Speech Delay - Arsita Sari, Galuh; Rohmah, Lailatu; Nadlifah, Nadlifah (ACIECE, 2019)
The purpose of this study is to describe the professionalism of teachers in improving children's speech delay in speech delay. This research was conducted at KB Ceria Timoho Yogyakarta. This research uses a descriptive qualitative approach. The results showed that the professionalism of teachers in dealing with child speech delay at KB Ceria Timoho Yogyakarta through training in early detection of child growth and development, improvement of facilities and infrastructure that support the development of children's language, care and additional facilities needed to support children's language development such as laptop games music, song beetles, tools for watching movies, story books, puppets for stories, presenting people from the education office for information about the curriculum and accreditation and enhancing learning programs by always innovating. The teacher's steps in improving children's speech ability "speech delay" at KB Ceria Timoho Yogyakarta is most important by knowing the cause of children talking too late because by knowing the cause the teacher is easy to handle it, not following the child's speech patterns is wrong, involving children talking at any circumstances, the teacher always makes eye contact when talking with children, the use of APE that supports children's vocabulary, holding parenting by presenting a pediatrician or child psychologist or can also consult with the teacher at any time especially when distributing child report cards